Development Of Sonic Air Flow Meter - Arumugam, Sagaathevan (Universiti Sains Malaysia, 2019)
To reduce the power consumption of air conditioning system, we can optimize the flow rate in air conditioning system. Thus, a device created to measure the flow rate to optimize the flow rate and increase the efficiency of the air conditioning system. The triangular obstacle will be simulated and will be compared with actual model to verify the setup of the experiment . In experiment, the optimum obstacle will be tested to determine variable such Sound power level (Db), Volumetric flow rate and Air velocity experiment, from microphone sound intensity generated in microphone and Fast Fourier Transform (FFT) used to transform intensity against frequency of sound wave graph. A peak of intensity exists at a certain frequency. Different flow rate gave different peak intensity of sound at same frequency of 2194Hz. After the experiment calibration graph of intensity of sound (dB) against flow rate at a specified frequency obtained as reference when using the sound acoustic to determine the velocity /flow rate in air conditioner in a more economical way